Treatment Delay in Rectal Cancer - Law, C.W.; Roslani, A.C.; Ng, L.L.C. (2009)
Early diagnosis of rectal cancer is important for prompt treatment and better outcome. Little data exists for comparison or to set standards. The primary objective of this study is to identify factors resulting in delays in treatment of rectal cancer, the correlation between the disease stage and diagnosis waiting time, treatment waiting time and duration of symptoms. A five year retrospective audit was undertaken in University of Malaya Medical Centre (UMMC). There were 137 patients recruited and the median time to diagnosis was nine days after the first UMMC Surgical Unit consultation with a mean of 18.7 days. Some 11% had to wait more than four weeks for diagnosis. The median time from confirmation of diagnosis to surgery was 11 days with a mean of 18.6 days. Sixty-two percent of patients were operated upon within two weeks of diagnosis and more than 88% by four weeks. However, 10% of them had delayed surgery done four weeks after diagnosis. Long colonoscopy waiting time was the main cause for delay in diagnosis while delay in staging CTs were the main reason for treatment delays.